Comportamento coordenado e individual em duplas de ratos sob esquema de intervalo variável - Santos, Letícia dos (Universidade Federal de São Carlos, 2021)
The combined behavior of two or more individuals is subject to selection by the consequences of the environment, in the same way as individual operant behavior. Previous studies used an interdependence procedure to investigate the response- reinforcement relationship and the effects of the type of reinforcement schedule on coordinated behavior. One of the studies investigated the effects of parametric manipulation in a fixed-ratio schedule (FR 1, 6, 12, 18, 24, 30, 50, and 70), on the performance of pairs of rats, under two conditions, one that required temporally coordinated responses of the two members of each pair, and another in which the reinforcer was delivered for independent individual responses (Coordinated versus Individual Condition). The results obtained showed that the function that relates the total rate of responses to the size of the reinforcement ratio had an inverted U shape, both for coordinated responses and for the responses of rats that worked individually, replicating the function obtained with individual organisms in previous studies. The coordinated response patterns also replicated those obtained with individual organisms: the higher the ratio of the schedule, the higher was post-reinforcement pauses. Considering researches on coordinated responses and reinforcement schedules, the present study aimed to investigate coordinated behavior as a function of parameters of variable-interval schedules (VI), that generates different patterns from the FR schedules, aiming to increase the understanding of selection processes of coordinated responses among rats. Planned as a systematic replication, where the main variable now is the rate of reinforcement and its variable distribution, the study explored the VI 5, 10 s, 20 s, 40 s, and 80 s intervals for a condition with no coordination requirement among rats, and the VI 5 s, 10 s, 20 s, 40 s, 60 s, 80 s, 120 s, 160 s and 320 s for a condition with a coordination requirement among the pairs, which were compared to each other. Six pairs of rats were used, three pairs for each condition. The results obtained indicated a bitonic function, in an inverted U shape, which relates response rate and reinforcement rate, replicating data from the extensive literature on the VI schedule for individual responses. This function was observed in the global response rates for the Coordinated Condition and Individual Condition, in the rate of coordinated and “equivalent” responses to the coordinated responses, and in the percentage of coordinated responses in both conditions. In addition, it was observed that the contingency of the schedule that required coordination had a relevant role in the selection of the coordinated response among the pairs, generating higher rates and percentages of coordinated responses when compared to the data of the subjects exposed to the individual schedule. The results extend the research line that has been investigating coordinated responses patterns under intermittent schedules of reinforcement.
Coordinated and individual behavior of pairs of rats under variable-interval schedule of reinforcement
Keywords: Comportamento coordenado; Esquemas de reforço; Intervalo variável; Água; Ratos; Coordinated behavior; Schedules of reinforcement; Variable-interval; Water; Rats; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO